Direct electron transfer of Phanerochaete chrysosporium cellobiose dehydrogenase at platinum and palladium nanoparticles decorated carbon nanotubes modified electrodes. Issue 37 (1st September 2015) - Bozorgzadeh, Somayyeh; Hamidi, Hassan; Ortiz, Roberto; Ludwig, Roland; Gorton, Lo
Abstract : Present work describes an efficient electrical connection of a class I cellobiose dehydrogenase on graphite electrodes modified with MWCNTs decorated with Pt and Pd nanoparticles. Abstract : In the present work, platinum and palladium nanoparticles (PtNPs and PdNPs) were decorated on the surface of multi-walled carbon nanotubes (MWCNTs) by a simple thermal decomposition method. The prepared nanohybrids, PtNPs–MWCNTs and PdNPs–MWCNTs, were cast on the surface of spectrographic graphite electrodes and then Phanerochaete chrysosporium cellobiose dehydrogenase ( Pc CDH) was adsorbed on the modified layer. Direct electron transfer between Pc CDH and the nanostructured modified electrodes was studied using flow injection amperometry and cyclic voltammetry. The maximum current responses ( I max ) and the apparent Michaelis–Menten constants ( K appM) for the different Pc CDH modified electrodes were calculated by fitting the data to the Michaelis–Menten equation and compared. The sensitivity towards lactose was 3.07 and 3.28 μA mM −1 at the Pc CDH/PtNPs–MWCNTs/SPGE and Pc CDH/PdNPs–MWCNTs/SPGE electrodes, respectively, which were higher than those measured at the Pc CDH/MWCNTs/SPGE (2.60 μA mM −1 ) and Pc CDH/SPGE (0.92 μA mM −1 ). The modified electrodes were additionally tested as bioanodes for biofuel cell applications.